The Role of Civil Law in Resolving Business Disputes in Court and Arbitration: A Comparison - Rodiatul Adawiyah Harahap; Dhea Ananada Puspita Yusuf; Afwan Lutfi Natoras Pohan; Zaidan Azmi; Surya Rahman Lubis (ISNU Sumatera Utara, 2024)
Business disputes can be resolved outside the court by arbitration and in court. What is the role of civil law as a basis for resolution. This research is descriptive normative research. The types and sources of legal materials used are secondary data. The technique for collecting legal materials uses library research. The legal material analysis technique used is normative. Settlement of business disputes can be carried out using the alternative of arbitration, then if it cannot be resolved then it is resolved in court.